2003
DOI: 10.17796/jcpd.27.3.dm4v13441p161928
|View full text |Cite
|
Sign up to set email alerts
|

Failure of eruption of first and second permanent molars

Abstract: Failure of eruption of permanent molars is an uncommon condition with a range of possible causative factors. This retrospective study of 35 pediatric subjects assesses the influence of these factors in the prognosis. The study aims to broaden our understanding of an abnormality, which has a considerable clinical impact, and proposes a treatment protocol for the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 17 publications
2
63
0
6
Order By: Relevance
“…However, in 1991, Nakamura et al (7) advocated multiple rosetting of molar teeth in patients diagnosed with mucopolysaccharidoses and related disorders. The management recommended for impacted molars comprises removal of the overlying bone or the mucosa and luxation and removal of the unerupted molar (8). In the case presented here, the impacted 38 was surgically removed under local anesthesia and the patient is currently undergoing orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 1991, Nakamura et al (7) advocated multiple rosetting of molar teeth in patients diagnosed with mucopolysaccharidoses and related disorders. The management recommended for impacted molars comprises removal of the overlying bone or the mucosa and luxation and removal of the unerupted molar (8). In the case presented here, the impacted 38 was surgically removed under local anesthesia and the patient is currently undergoing orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The impacted tooth is far more common in permanent than primary teeth. The impacted mandibular first molar accounts for only < 0.01% of the population, so it is a rare occurrence 3) . Proffit and Vig 4) reported that the rate of impacted teeth was higher for posterior teeth than anterior teeth.…”
Section: ⅲ Discussionmentioning
confidence: 99%
“…The treatment for failure of eruption of permanent molars depends on several factors, the most important being age 5. Treatment options include observation, extraction of the obstacle, surgical exposure, luxation and extraction of the unerupted molar 13.…”
Section: Discussionmentioning
confidence: 99%